Biosynthesis of copper nanoparticles from areca nut extract and its antibacterial and antioxidant properties - Pradeep, Bhavana; Hemba, Priyanka; Jagadeesh, Anusha Kunnathuli; Ramakakanavar, Chaitra Ganappa; Nayak, Sneha; Rao, Chandrayan Vaman (Agriculture and Natural Resources, 2019)
The phytochemicals present in different maturity stages of areca nut (Areca catechu) were evaluated. Phytochemical tests revealed the presence of carbohydrates, alkaloids, flavonoids, tannins and phenolic compounds. Copper nanoparticles were biosynthesized from the matured areca nut extract and characterization of the synthesized nanoparticles was carried out by analyzing the surface plasmon resonance, particle size and zeta potential. Field emission scanning electron microscopy and Energy dispersive X-ray analysis (EDAX) of nanoparticles synthesized from only stage 5 areca nut extract were used because this stage produced the highest antibacterial activity. The antibacterial activity of nanoparticles and the extract was tested against Gram-positive and Gram-negative bacteria; the plain extract had a zone of inhibition of 10–13 mm, whereas biosynthesized copper nanoparticles had a zone of inhibition of 23–25 mm. The nanoparticles also had enhanced antioxidant activity compared to plain areca nut extract and thus, the extract has potential for use as an antioxidant agent in pharmaceuticals and cosmetics. It can be concluded from this study that by using a nanotechnological approach, phytochemicals found in areca nut could be put to good use to enhance their antibacterial and antioxidant activity.